Elsa Morante and Arthur's Island - İlhan KARASUBAŞI (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
Arturo's Island written by the famous Italian woman writer of the XX. century Elsa Morante respects her life vision and literature understanding by observing everyting from the point of view of children woman and man in by using autobiogracal traces to the reader. Her work after the stories titled The Thief of lights 1935, The Glassed Man 1936, The Grandmother 1937, The Hidden Joke 1963 and The Andalusian Scarf enriched with supplementary editions and together with The History 1974 in which the common content is mainly the member of the society and the difculties especially of woman living in men dominated society. The aim of this work is the observation of Works with a descriptional manner presented by Elsa Morante to the lecturer.